GAMBARAN PENGETAHUAN SIKAP DAN PERILAKU PEMELIHARAAN KESEHATAN GIGI DAN MULUT PADA KOMUNITAS ANAK JALANAN TANPA BATAS BANDUNG (Politeknik Kesehatan Kemenkes Bandung, 2020)
Street children are children who spend most of their time on the streets working, playing or doing other activities. Street children live on the streets because they have been dumped or dumped by families who cannot afford the burden of poverty, most of their time is spent on the streets, so paying attention to their oral health is very limited. This type of research is descriptive research. The study population was all street children in the Bandung Boundary Community. The research sample was taken by accidental sampling technique with a total sample of 7 people. Data obtained from the results of the questionnaire respondents regarding knowledge, attitudes and behaviors of oral health. After that, the data generated is processed, and presented in the form of a frequency distribution table. The results showed that the results of the knowledge questionnaire score had good criteria, while attitudes and behavioral scores contained moderate criteria, it showed that the description of knowledge, attitudes and behaviors of dental and oral health of street children must be maintained at a moderate criteria, and would be better if improved from being good, it is influenced by factors of understanding and awareness of each respondent